RANCANG BANGUN GRIPPER ROBOT MANIPULATOR 2 DOF KAPASITAS 1,25 KGF - Sirojuddin Sirojuddin; Siti Solikhah; Ragil Sukarno; Muhammad Izaz Tamami (Jurnal Rekayasa Mesin, 2023)
Manipulator robots practically help human to move objects vertically, horizontally, or rotationally. The robot is generally divided into three components, namely arm, base, and gripper with servo motor drive. The aim of this study is to improve the previous gripper robot manipulator design so that it can move 2 DOF (Degree of Freedom) by adding 1 DOF located on the robot gripper, which in previous studies, the robot manipulator gripper was only able to move 1 DOF. In addition, after calculating using Von Mises theory, then design 2D components and this assembly using AutoCAD software. Next design 3D components and assembly using Autodesk Inventor application based on FEM (Finite Element Method). Will also make a tool in the form of a robot gripper which will later be tested for feasibility. Based on the calculating result, the minimum thickness of the most significant link is 5.1 mm. To make it easier to find plates and save costs, the thickness of all plates in each link is rounded up to 6 mm. From the result of the movement simulation, it is found that the gripper can move open, clamp and rotate, and from the FEM software result the Safety factor value = 3.58 >3.0. Meanwhile, based on the result of the feasibility test, the gripper robot manipulator is feasible.